A Novel Generative Design System for Ceiling Lighting Layouts - Alhamarna, Sara (2020)
The dissertation suggests a novel design approach that generates reflected ceiling layouts. Presenting an algorithmic system scripted Dynamo in the form of a BIM plug-in. The system employs various design approaches through transferring selected design concepts into mathematical scripts in Dynamo software, resulting in a production of two-dimensional lighting layouts in Dynamo.